Analisis tipe gerakan tanah pada lereng Bendungan Bulango Ulu Kabupaten Bone Bolango menggunakan metode kinematika - Moehammad Jasim Agi Saputra; Aang Panji Permana; Noviar Akase (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The Bulango Ulu Dam is one of the strategic projects built in Tuloa Village, North Bulango District, Bone Bolango Regency, Gorontalo Province. In building a dam, geological analysis and slope stability are very important to avoid the risk of collapse or structural failure. This research aims to conduct geological analysis and slope stability at the Bulango Ulu Dam using kinematics methods. The kinematics method is used to determine the type of ground movement on the dam slope and identify the probability value of failure. Geological data related to lithology, petrography, geological structure and geomorphology are collected through direct observations and in the laboratory. Then, this data is used to determine geological conditions, geological structure and geomorphology which are then interpreted in relation to slope stability. The research results show that the geomorphological units are alluvial plains and low structural hills. The lithology that makes up the slopes of the Bulango Ulu Dam is composed of alluvial units and granodiorite units. The geological structure that develops is in the form of tensile joints in a general direction east-west (E-W) and cut by tension joints in a general direction north-south (N-S). The type and probability of ground movement that occurs based on segment, namely on segment A-B slopes in the form of Wedges (21.65%), segment B-C slopes in the form of Wedges (12.27%), segment E-F slopes in the form of Wedges (15.12%), and segment slopes G-H is a Wedge (21.8%). Based on the results of kinematic and boundary equilibrium analysis, the slopes on the Bulango Ulu dam are in the stable category. This research recommends that there is no need to make changes to the geometry of the dam slope because the slope is in a stable condition.